IMPROVEMENT OF A WEEDHOPPER 2 ULTRALIGHT AIRCRAFT BY USING MODERN MATERIALS - Mihalić, Tihomir; Kostadin, Tihana; Runje, Vedran (Journal of Energy Technology, 2024)
The goal of this research was to make airworthy, to modify, and to improve the performance of a Weedhopper II ultralight aircraft (ULA) (JC-24)) manufactured in 1986. In this paper, the renovation of the existing construction and improvements with the use of modern materials and current construction techniques have been carried out. This improved the aircraft performance and removed some of the original design defects. The whole avionics system has been replaced. As the usage of composite materials has resulted in a decrease in the total mass, the determination of the new centre of gravity was carried out to ensure that the airplane remains balanced after being modified. Keeping the weight of the aircraft within the prescribed limit and ensuring that aircraft is in balance has a profound impact on flight safety. The position of the Airplane Centre Stick was changed to increase pilot ergonomics. Then, with the inspection of the engine, it was found that the replacement of the engine carrier was necessary, and the construction and production of the new carrier were performed. Furthermore, an appropriate propeller was selected, and the gearbox ratio was checked. The performances of the propeller have been measured experimentally. The construction of the trimmer of the vertical rudder was made in order to balance the aircraft. Before the flight test, aircraft balancing was performed.